FORMULASI TABLET HISAP EKSTRAK ETANOLIK DAUN KEMANGI (Ocimum sanctum L.) DENGAN VARIASI PEMANIS MANITOL DAN LAKTOSA - Devi Nisa Hidayati; Lusyana Setiawati Marwan; Mufrod Mufrod (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2015)
ABSTRACT Holy  basil  leaves  (Ocimum  sanctum  L.)  traditionally  used  by  the  people  as  a  stomatitis aphtosa medication. Bacteria could cause stomatitis aphtosa. Flavonoids in holy basil leaves had antibacterial activity. The usage of holy basil leaves traditionally were not practice so formulated more  acceptable  such  lozenges.  Acceptability  is  influenced  by  a  taste.  This  study  aims  was  to determine sweeteners variations which  is mannitol and  lactose from   the lozenges formulation of holy basil leaves extract on the physical properties and the level of consumer acceptance taste. Holy  basil  leaves  extract made  by maceration method  using  70%  ethanol.  Lozenges made within  5  based  on  the  variation  concentration  of mannitol  and  lactose  are FI  (100%:0%),  FII (75%:25%),  FIII  (50%:50%),  FIV  (25%:75%),  dan  FV  (0%:100%)  and  manufactured  by  wet granulation method. The granules obtained were tested for physical properties include flowability, angle  of  repose,  and  compressibility.  The  tablets  obtained  were  tested  for  physical  properties including  weight  uniformity,  hardness,  friability,  dissolve  time,  responsive  taste  test,  and  the active substance with TLC methods. The data obtained were analyzed statistically using one way ANOVA and Kruskal Wallis, except acceptability taste analyzed descriptionally.   The  results  showed  that  all  formulas  provide  lozenges  which  conform  the  quality specification. Lozenges most accepted by the respondents was formula I. Keywords: holy basil leaves, lozenges, mannitol, lactose